Performing the Komagata Maru: Theatre and the Work of Memory - Murphy, Anne (Studies in Canadian Literature, 2015)
This essay explores a performance of commemoration of the “Komagata Maru incident,” an event named for a ship that was the centre of controversy in 1914 when it arrived in the port of Vancouver bearing 376 would-be immigrants to Canada from British India. Most of the passengers on the ship were disallowed from entering Canada under three orders-in-council passed by the Dominion Government that amended Canada’s Immigration Act, as a part of a broader move against Asian immigration in the period. The essay focuses on a production developed and performed for the centenary of the arrival of the Komagata Maru out of a partnership between the Departments of Asian Studies and Theatre and Film at UBC; Rangmanch Punjabi Theatre, based in Surrey; and Srishti Institute for Art, Design and Technology in Bangalore, India. The production wove together selections from three Canadian theatrical representations of the event: “The Komagata Maru Incident” by Sharon Pollock (1976; in English), “The Komagata Maru” by Ajmer Rode (1984; in Punjabi), and “Samuṅdarī sher nāl takkar” or “Conflict with the Sea Lion,” co-authored by Sukhwant Hundal and Sadhu Binning (1989; in Punjabi). The plays, in conversation, act as a lens through which we can see how memory produces the present, and how the performed past creates possibilities for creative engagement with the present and future.